Dermatosis associated with menopause - Pragya A Nair (Wolters Kluwer Medknow Publications, 2014)
Menopause is defined as permanent irreversible cessation of menses brought by decline in ovarian follicular activity. Hormonal alteration results in various physical, psychological, and sexual changes in menopausal women. Associated dermatological problems can be classified as physiological changes, age-related changes, changes due to estrogen deficiency and due to hormone replacement therapy. Dermatosis seen due to estrogen deficiency includes Atrophic Vulvovaginitis, Vulvar Lichen Sclerosus, Dyaesthetic Vulvodynia, Hirsutism, Alopecia, Menopausal Flushing, Keratoderma Climactericum, Vulvovaginal Candidiasis. Dermatologists and gynecologists need to be familiar with the problems of menopausal women, as with increase in life expectancy, women passing through this phase is rising.